2010
DOI: 10.1158/1055-9965.epi-10-0407
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Vitamins B2, B6, and B12, and Related Genetic Variants as Predictors of Colorectal Cancer Risk

Abstract: Background: B-vitamins are essential for one-carbon metabolism and have been linked to colorectal cancer. Although associations with folate have frequently been studied, studies on other plasma vitamins B2, B6, and B12 and colorectal cancer are scarce or inconclusive.Methods: We carried out a nested case-control study within the European Prospective Investigation into Cancer and Nutrition, including 1,365 incident colorectal cancer cases and 2,319 controls matched for study center, age, and sex. We measured th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
59
3

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 61 publications
(72 citation statements)
references
References 59 publications
10
59
3
Order By: Relevance
“…These results are similar to the findings of our previous report from the same population (9,31). Two prospective studies of circulating vitamin B12 have been published since, none of which found a statistically significant association between vitamin B12 and colorectal cancer risk (11,43).…”
Section: Discussionsupporting
confidence: 91%
“…These results are similar to the findings of our previous report from the same population (9,31). Two prospective studies of circulating vitamin B12 have been published since, none of which found a statistically significant association between vitamin B12 and colorectal cancer risk (11,43).…”
Section: Discussionsupporting
confidence: 91%
“…Although reverse causality is a potential bias in a cross-sectional setting, colorectal adenoma is a preclinical disorder, which most likely has no systemic effects influencing one-carbon metabolism and related B-vitamins. Moreover, the inverse associations of vitamins B2 and B6 with colorectal adenoma are in line with observed inverse associations with colorectal cancer in prospective studies (25,27).…”
Section: Strengths and Weaknessessupporting
confidence: 71%
“…Vitamin B12 status was not associated with colorectal cancer in the majority of the studies (21,(24)(25)(26). In addition, plasma vitamin B2 has been reported to be not associated (24) or inversely associated (25) with colorectal cancer risk. On the other hand, vitamin B6 has consistently been associated with reduced colorectal cancer risk, as indicated by a recent meta-analysis on prospective studies (27).…”
Section: Introductionmentioning
confidence: 90%
“…[10][11][12] The other B vitamins have been little studied. 2,13 Calcium and vitamin D have been extensively studied in relation to the risk for colorectal cancer. 2 Several previous prospective studies have observed inverse associations of dietary calcium and of serum and dietary vitamin D with risk for colorectal cancer, 2,14 but the Women's Health Initiative randomized controlled trial did not find evidence of benefit with supplemental calcium and vitamin D, 15 and neither dietary calcium nor dietary vitamin D was associated with risk in our analysis.…”
Section: Discussionmentioning
confidence: 99%